(untitled) (Research, Society and Development, 2020)
This research aimed to identify the patient’s perception of the assistance provided in the Surgical Center and Post-Anesthetic Recovery Room. This is a descriptive study, with a qualitative approach, carried out with 59 patients who underwent surgery at the Surgical Center of a University hospital located in southern Brazil. Data collection occurred through an interview based on a semi-structured instrument. Data analysis was performed based on content analysis, thematic type. It was evidenced that the study comprises the patient’s perception in relation to the care in the operating room, considering that based on how the patient feels in his surgical experience, it will be his future perceptions. In this sense, the results obtained in this study demonstrate the importance of providing quality care. It is expected that this study will contribute to the development of safer and more humanized care, focused on the needs of each patient.